The hospital admissions study in England: are there alternatives to emergency hospital admission?. Issue 2 (April 1995) - Coast, J; Inglis, A; Morgan, K; Gray, S; Kammerling, M; Frankel, S
Abstract : STUDY OBJECTIVE--To assess the potential for substituting alternative forms of care for admission to an acute hospital in particular groups of patients. DESIGN--A screening tool, the intensity-severity-discharge review system with adult criteria (ISD-A), developed for hospital utilisation review in the USA, was used in a cohort of hospital admissions to identify a group of patients who could potentially have been treated outside the acute hospital. These patients were further assessed by a panel of general practitioners (GPs) to determine the most appropriate alternative form of care. A cost analysis was performed on the results obtained. SETTING--General medicine and geriatric specialties in one acute hospital in the south western region. PATIENTS--Patients comprised a sample of 701 admitted to general medical and geriatric specialties. MAIN RESULTS--The screening tool identified 19.7% of admissions for whom there was potential for treatment outside the acute hospital. Assessment by the GP panel reduced this potential to between 9.8% and 15.0% of emergency admissions. The alternatives most frequently identified as "most appropriate" were the community hospital/GP bed and the urgent outpatient assessment (within either 24 or 48 hours). Potential resource savings based on the average cost were relatively small. This potential seemed to be greater for the alternative of the urgent outpatient assessment. CONCLUSIONS--Potential exists for treating a proportion of patients in lower intensity alternatives to the acute hospital. If this potential were exploited few resource savings would occur.